Community Empowerment through Research, Innovation and Open Access Proceedings of the 3rd International Conference on Humanities and Social Sciences (ICHSS 2020), Malang, Indonesia, 28 October 2020 - Sayono, Joko; Taufiq, Ahmad; Sringernyuang, Luechai; Sismat, Muhamad Alif Haji; Isma'il, Zawawi; Navarro, Francis M.; Purnomo, Agus (Taylor & Francis, 2021)
ICHSS is an international seminar that is held every two years organized by the Research and Community Service Institute of the State University of Malang. The meeting aims to discuss the theoretical and practical developments of Social Sciences and Humanities in Indonesia and other countries with a view to build academic networks by gathering academics from various research institutes and universities. Community empowerment serves as a trigger to increase community independence and to cope with the challenges resulting from the rapid development of technology. An important aspect of the community empowerment effort is to link the results of innovation research for the benefit of community. The results of research should not only be limited to publications in the academic environment. Open Access to various forms of the existing literature is one of the requirements for innovative research to develop optimally. Therefore, this seminar has also served as a place for field researchers from various geographical areas to socialize, to discuss and to find solutions to current issues in the field of social sciences and humanities, as well as to build cooperation and synergy in creating ideas for mutual collaboration and to create joint research.